การบังคับคดีปกครองก่อนและหลังการจัดตั้งศาลปกครอง - อภิรดี พลอยเลื่อมแสง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of the establishment of the Administrative Court is to control and examine the legistimacy of law , unlawful administrative action , remedy the grave injury and settle the dispute. In order to achieve the purpose, the execution of the administrative court judgment should have effectiveness to settle the efficiency along with the court’s purpose. However, the execution of the administrative court judgment still have some problems and obstacles from (1) problem in law or rule incompleted in administrative execution (2) Problem in authority and functional exercising of administrative court (3) problem from parties and (4) problem occured from performing the administrative execution of the office of the administrative court. The result of this thesis suggested the guideline to solve these problems in administrative execution focusing on the administrative court judgment and comparing with the administrative enforcement before the adminstrative court was established, which the authority to enforcement of judgment is operated by the court of justice and the petition commission, the author recommended that the administrative court executive measures or method should have improved in order to remedy the grave injury of the parties and settle the dispute. This thesis suggested the solutions as follows (1) the administrative court should disserminate the understanding of the administrative execution to the related administrative agencies (2) the office of the administrative court should inform the authorites and duties about the execution to the court (3) provided the clarity criteria and methods in administrative execution (4) added the measure or method in administrative execution and (5) applied the executive substitution measure case by case.